Avaliação dos efeitos da exposição aguda aos agrotóxicos 2,4 D e Fipronil em brânquias de Danio rerio - Viana, Natália Prudêncio (2020)
The pesticides used in monocultures have the main function of reducing losses during the production process. These compounds can affect a wide spectrum of plant and animal species, inducing from biochemical and morphological changes to bioconcentration in tissues, which can lead to the death of these organisms. Thus, biochemical and histological analyzes of bioindicator organisms become effective tools for determining the impact of these substances. In this work the fish Danio rerio, a biological model used worldwide in toxicological tests, was chosen to assess the impact of concentrations of environmental relevance of two pesticides used in sugarcane monocultures in Brazil, fipronil and 2,4-D, tested alone and in mixture. Fipronil and 2,4-D bioconcentrate in the body of D. rerio, with a bioconcentration factor (BCF) of 1,092 for fipronil, 1,373 for 2,4-D alone; in mixture, BCF presented values of 1.261 and 1.005 for the insecticide and herbicide, respectively. Gills of fish exposed to fipronil showed a decrease in catalase activity and increased when exposed to the herbicide. In mixture, there was an increase in the activity of glutathione-S-transferase in samples of gills and of the whole body, in addition to the increase observed in the activity of acetylcholinesterase in D. rerio muscle. The gills of the exposed fish had histopathological changes and an increase in the fractional area of the chloride cells. The results obtained show responses of D. rerio when exposed to the insecticide and herbicide for 96 h, indicating that pesticides pose a risk to fish health in environmentally relevant concentrations.